Biodiversidade de macrófitas aquáticas em uma área úmida ecotonal - AROUCHE, Marlla Maria Barbosa (2021)
The Baixada Maranhense lowland is one of the largest wetlands in Maranhão, having the largest set of lacustrine basins in the Northeast, having worldwide importance as a conservation hotspot, being elected as one of the Ramsar sites in Brazil, it is also referred to as "Pantanal Maranhense" comprising approximately 20 thousand km² within the Legal Amazon of Maranhão). Aquatic macrophytes are an important part of this ecosystem, they are plants visible to the naked eye, whose active photosynthetic parts are permanently, or for several months, every year, totally or partially submerged in fresh or brackish water, or floating. In the Baixada Maranhense lakes, floristic and ecological studies of aquatic macrophytes are necessary to understand the dynamics of communities, since these plants play the role of primary producers in the food chain, producing a lot of biomasses, and directly contributing to increased diversity. To ensure proper management aiming at the conservation of aquatic macrophyte species in Maranhão, studies aimed at understanding the species are necessary, together with studies involving taxonomy and ethnobotany. The correct identification of species can, in addition to informing the existing richness, subsidize data about species of economic, biological and especially plant importance that can be used as long-term indicators with a high spatial spectrum. This study aims to list the aquatic plants from the southwestern region the APA of Baixada Maranhense, comparing them with other humid natural areas in the Amazon region. The checklist was generated from exploratory collections carried out in the study area and complemented with records from the database of virtual herbaria as well as those from the Reflora (http://reflora.jbrj.gov.br/reflora/) e GBIF (https://www.gbif.org/) using the following descriptors: “macrophytes”, “aquatic”, “swamp”, “flooded”, “lake”, “river” and “brejo” (in Portuguese and in English). Articles and book chapters that presented floristic lists to be added to the checklist were also consulted. For the analysis of hierarchical clustering based on arithmetic mean (UPGMA), the Jaccard distance index was used. 107 species, 78 genera and 37 families were identified. The most representative families were Fabaceae, Cyperaceae and Poaceae. Among the inventoried species, two species had their occurrence recorded for the first time in Maranhão, which are: Hydrocleys modesta and Bauhinia catingae. After the analysis, it was observed that the area presented a difference between the Amazonian areas and the southwest of Baixada Maranhense. The hydrological dynamics and geographic proximity can be related to the similarity found between the studied areas. The predominance of aquatic species with wide distribution was observed, also seen in other wetlands in Brazil. Species from the Amazon and Savana were recorded, indicating the ecotonal condition of Maranhão. These data highlight the importance of the area for the conservation of aquatic macrophytes in the State.